Genome-wide analysis of apple CNGC family allows the identification of MdCNGC15A negatively regulating apple salt tolerance - Lina Qiu; Chuang Mei; Zhiping Qi; Jiaxin Yang; Na Li; Ming Li; Yunxia Sun; Jie Yang; Fengwang Ma; Ke Mao (Plant Stress)
Calcium (Ca2+) is essential for signal conduction and plant growth. Cyclic nucleotide-gated channels (CNGCs) are Ca2+ transporters that regulate Ca2+ signalling and homeostasis by modulating its transmembrane transport, thereby influencing plant development as well as the biotic and abiotic stress responses. Although identified in numerous plant species, the CNGC family has not been characterized in apple until now. Here, 20 MdCNGCs were identified from the apple genome and were randomly distributed on 13 chromosomes. Phylogenetic analysis classified these MdCNGCs into five groups (I, Ⅱ, Ⅲ, Ⅳ-a, and Ⅳ-b), with five pairs of segmental duplicated genes being detected via collinearity analysis. Sequence alignment and analyses of gene structures, conserved motifs, and 3D structures indicated high structural conservation, particularly within groups. Yeast two-hybrid (Y2H) assays demonstrated interactions between most MdCNGCs and the Ca2+ receptor MdCaM7.1, except for MdCNGC1B and MdCNGC15A. Promoter analysis and expression profiling revealed significant responses to abiotic stress, particularly salt stress, in some MdCNGCs. Silencing MdCNGC15A significantly enhanced apple plants salt tolerance, while its overexpression in apple calli significantly decreased tolerance, as shown by transgenic analysis. Collectively, our results demonstrate the crucial role of MdCNGCs in abiotic stress responses and provide valuable insights for future functional and regulatory studies in apples.